2004
DOI: 10.1021/jp044772j
|View full text |Cite
|
Sign up to set email alerts
|

Ni−V2O5·nH2O Core−Shell Nanocable Arrays for Enhanced Electrochemical Intercalation

Abstract: We have prepared Ni-V(2)O(5).nH(2)O core-shell nanocable arrays for Li(+) intercalation applications. Ni-V(2)O(5).nH(2)O nanocables were prepared via formation of Ni nanorod arrays through the template based electrochemical deposition, followed by coating of V(2)O(5).nH(2)O on Ni nanorods through electrophoretic deposition. Transmission electron microscopy (TEM) micrograph clearly shows the Ni core was covered completely by a V(2)O(5).nH(2)O shell. Electrochemical analysis demonstrates that in a current densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 23 publications
2
70
1
Order By: Relevance
“…Thermodynamically it is favorable for the crystalline nanoparticles to aggregate epitaxially; such growth behavior and mechanism have been well reported in literature. [66,67] [69] Ni nanorod arrays were first grown by the templatebased electrochemical deposition. In the second step, the hydrated vanadium pentoxide shell was deposited onto the surface of nickel nanorods through sol electrophoretic deposition.…”
Section: Reviewmentioning
confidence: 99%
“…Thermodynamically it is favorable for the crystalline nanoparticles to aggregate epitaxially; such growth behavior and mechanism have been well reported in literature. [66,67] [69] Ni nanorod arrays were first grown by the templatebased electrochemical deposition. In the second step, the hydrated vanadium pentoxide shell was deposited onto the surface of nickel nanorods through sol electrophoretic deposition.…”
Section: Reviewmentioning
confidence: 99%
“…Both energy density and power density of such nanocable-array electrodes are higher than those of single-crystal V 2 O 5 nanorod array and sol-gel-derived V 2 O 5 film. Such significant improvement in electrochemical performance is due to the large surface area and short diffusion lengths offered by the V 2 O 5 · nH 2 O shell [13]. Chou et al reported V 2 O 5 nanomaterials including nanoribbons, nanowires, and microflakes by an ultrasonic assisted hydrothermal method.…”
Section: -D Cathode Materialsmentioning
confidence: 99%
“…No electron diffraction pattern in TEM was observed, which suggests the amorphous nature of these nanotubes. Figure 6 shows the SEM micrographs of Ni nanorod arrays and Ni-V 2 O 5 core-shell nanocable arrays [28]. Ni nanorod arrays were grown in PC membrane by electrochemical deposition from nickel sulfate solution.…”
Section: Single Crystal Oxide Nanorod Arraysmentioning
confidence: 99%